Physical activity patterns and function 3 months after arthroscopic partial meniscectomy - Ilich, S; Dempsey, A; Mills, P; Sturnieks, D; Stachowiak, Gwidon; Maguire, K; Küster, M; Lloyd, D (Elsevier Australia, 2013)
Objectives: To compare physical activity levels, subject-reported function, and knee strength in 21 arthroscopic partial meniscectomy (APM) patients (age 45.7 (6.06) years, BMI 27.3 (5.96) female 60%) 3 months post-surgery with 21 healthy controls (age 43.6 (5.71) years, BMI 24.5(4.2) female 60%) matched at the cohort level for age, gender and BMI. Design: Case control study. Methods: Physical activity intensity, number of steps, and minutes spent in activity were objectively quantified using an accelerometer-based activity monitor worn for 7 days. The Knee Injury and Osteoarthritis Outcome Score (KOOS) and concentric quadriceps strength were used to evaluate function post-surgery. Differences in activity levels and functional outcomes between the APM and control participants were assessed using t-tests, while multiple linear regression was used to quantify the best predictors of physical activity. Results: APM patients engaged in a similar duration of activity to controls (469.0 (128.39)min vs. 497.1 (109.9)min), and take a similar number of steps per day (9227 (2977) vs. 10,383 (3501), but performed their activity at lower levels of intensity than controls. Time spent in moderate (r2=0.19) and hard (r2=0.145) intensity physical activity was best predicted by the Symptoms sub-scale of the KOOS for both controls and APM patients. Conclusions: APM patients participate in similar levels of activity at lower intensities, but with reduced activity at higher intensities which is related to the presence of symptoms of knee osteoarthritis.